Layanan Kesehatan Digital Pascapandemi melalui Pusat Koordinasi dan Informasi Covid-19 Jawa Barat (Pikobar) - Sindy Valenita; Endah Mustika Ramdani; Joni Dawud; Nita Nurliawati (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2022)
Pusat Koordinasi dan Informasi Covid-19 Jawa Barat (Pikobar) application system is an example of digital services implementation in West Java. Since pandemic condition has been improving, thus, Pikobar application needs system adjustment. This research was carried out at Jabar Digital Service (JDS) as theÂ  developer and organizer of Pikobar, to analyze Pikobar services so that they can be used in post-pandemic era. The aim of this research was to look at the potential of JDS to create services that suit the need of the community, especially digital health services. The research method was descriptive and qualitative through interviews and observations. This study used successful service strategy model according to Devrye (1997), which consisted of seven aspects, namely: Self-esteem, Exceeded expectations, Recovery, Vision, Improving, Care, and Empowerment. The results showed that the seven aspects had been met by JDS, but there were still room for improvement. Pikobar service improvement can be used to adjust features made in the future with the support from various strategies, such as digital-based public service policies making, technology infrastructure support, and transforming Pikobar into health service center. Thus, in the long run, West Java citizen could use Pikobar as digital public service in postpandemic era.